"It must start with me, so it started with me": A qualitative study of Project YES! youth peer mentor implementing experiences supporting adolescents and young adults living with HIV in Ndola, Zambia. - Virginia M Burke; Christiana Frimpong; Sam Miti; Jonathan K Mwansa; Elizabeth A Abrams; Katherine G Merrill; Julie A Denison (PLoS ONE)
Background Little is known about youth-led approaches to addressing HIV-related outcomes among adolescents and young adults (AYA) living with HIV. In response, Project YES! hired and trained youth living with HIV as peer mentors (YPMs) in four HIV clinics in Ndola, Zambia to hold meetings with 276 15-24-year-olds living with HIV. Within this randomized controlled trial, a qualitative sub-study was conducted to explore YPMs' implementing experiences. Methods In-depth interviews were conducted with the eight YPMs (50% female) ages 21-26 years. YPMs were asked about their experiences working with clients, their feedback on program components, and what the experience meant to them personally and professionally. Interviews were audio-recorded, transcribed verbatim, and thematic analysis was performed. Results YPMs connected with AYA clients by discussing shared struggles, modeling positive health behaviors, and establishing judgement-free environments. YPMs experienced powerful personal transformations in HIV-related health behaviors, conceptions of self, and plans for the future. Many expressed now seeing themselves as community leaders-"ambassadors", "game changers"-and "not just alone in this world." They described newfound commitments to reaching personal and professional goals. YPMs were adamant that Project YES! should expand so other HIV-positive AYA might benefit. Conclusion Well-trained and compensated YPMs who are integrated into HIV clinics can support AYA in unique and important ways due to their shared experiences. The transformational experience of becoming YPMs empowers youth to see themselves as role models and leaders. Future programs should engage youth living with HIV as partners in efforts to end the HIV epidemic.